NEED OF EXTERNAL QUALITY ASSESSMENT SCHEME – AN EXPERIENCE IN CENTRAL LABORATORY AT RNTMC, UDAIPUR - JAKHAR, PRAGYA; RAJAK, VIJAY; DWIVEDI, GUNJA; MEENA, KIRAN (Asian Journal of Pharmaceutical and Clinical Research, 2024)
Objectives: The objectives of the study are to periodically assess the quality of the external quality assessment scheme (EQAS) with the aim of enhancing laboratory performances. Methods: An observational study was done at our central laboratory at RNTMC, Udaipur, after approval from the institutional review board. Our laboratory receives quarterly blood samples and already prepared slides from AIIMS, Delhi, for complete blood count (CBC). In addition, lyophilized blood samples for fibrinogen, prothrombin time/international normalized ratio (PT/INR), and activated partial thromboplastin time (APTT) analysis are received quarterly from CMC, Vellore, through courier package. As for cytopathology, the third package includes already prepared 10 slides of 2 cycles for cytopathology analysis along with a brief clinical history. Results: CBC, peripheral blood film examination findings, and reticulocyte count results were consistently acceptable, except in August 2021, December 2022, and March 2023 when some parameters of CBC were deemed unacceptable. Results for PT/INR, APTT, and fibrinogen were within consensus at all-time except in March 2022, when they were out within consensus and deemed unacceptable. Similarly, results for cytopathology evaluation were in concordance with the results of the provider except for a few occasions were deviations were seen for some diagnoses due to interpretation error. Conclusion: Engaging in EQAS has facilitated the enhancement of test result accuracy, thereby improving the overall quality of laboratory practices and minimizing erroneous outcomes.